PEMIKIRAN SYEKH NAWAWI AL-BANTANI DAN RELEVANSINYA DI ERA MODERN - Ahmad Wahyu Hidayat (Aqlam: Journal of Islam and Plurality, 2019)
Abstract This research elaborates the education in accordance to Sheikh Nawai Al-Bantani. This research used library research with analytical study method. Analytical Studies used are analytical content and analytical descriptions of education according to Sheikh Nawai Al-Bantani. The results can be seen from the ideas of Shaykh Nawawi Al-Bantani which includes: 1. The Existence of the Universe, 2. Human Potential, 3. Human Existence, 4. Educational Objectives and 5. The principles of Islamic educational activities. Islam in Indonesia will certainly be able to develop meaningful indigenous Islamic traditions, which will be truly Islamic and creative. There were signs that contain an expectation for the future in dynamic educational and intellectual activities based on the development of Islamic school and universities in Indonesia.Keywords : Biography, Education, Relevance. AbstrakPenelitian ini menjelaskan konsep pemikiran pendidikan menurut Syekh Nawawi al-Bantani. Penelitian ini menggunakan data kepustakaan dengan metode analisa konten dan analisa deskripsi tentang pendidikan menurut Syekh Nawawi al-Bantani. Hasil temuanya bisa dilihat dari ide-ide pemikiran pendidikan Syekh Nawawi al-Bantani yang meliputi: 1. eksistensi alam semesta, 2. potensi-potensi Manusia, 3. eksistensi manusia, 4. tujuan Pendidikan dam 5. prinsip-prinsip aktivitas pendidikan Islam. Pemikiran al-Bantani dapat berkontribusi dalam perkembangan tradisi Islam pribumi yang bermakna, yang akan benar-benar bersifat Islami dan kreatif.  Terdapat tanda-tanda yang mengandung harapan bagi masa depan aktivitas pendidikan dan intelektual yang dinamis didasarkan pada perkembangan sekolah dan universitas-universitas Islam yang berkembang di Indonesia.Kata Kunci: Biografi, Pendidikan, Relevansi.